Implications of Pyrite Oxidation for Engineering Works - Hawkins, A. Brian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The book highlights and analyses the distress to buildings caused by sulphate-induced heave, with particular reference to the recent problems in the Dublin area of Ireland. It describes the formation of pyrite, the processes involved in its oxidation and the various ways in which consequential expansion takes place. For the first time in the literature it discusses the way that buildings can be raised above their supporting foundation walls by the expansion of pyritiferous fill which has been used beneath ground-bearing floor slabs in Ireland. The significance of fractures through the iron sulphide microcrystals for the rate and extent of oxidation is discussed. Photographs and profiles of sulphate ingress into concrete/concrete blocks are presented. Case histories from the UK, North America and Ireland are discussed.
Engineering Implications of the Oxidation of Pyrite: an overview, with particular reference to Ireland -- Sampling Potentially Pyritiferous Materials -- Testing of Potentially Pyritiferous Material -- Problems Associated with the Use of Pyritiferous Fill at Ballymun Youth Facility, Dublin -- Remediation of Senior Citizens$1 (BDwellings affected by Pyrite-Induced Heave -- The Effect of Pyrite-Related Heave: A Structural Engineer$1 (Bs Perspective -- The Canadian Pyrite Experience and Comparisons with the Irish Problems -- Pyrite Oxidation and Structural Problems in the Chattanooga (Ohio) Shale, East Central Kentucky -- Iron Sulphides and Surface Heating: Further Engineering Considerations for the Dublin area.s
Keywords: Geography; Civil engineering; Hydraulic engineering; Environmental sciences; Earth Sciences; Geotechnical Engineering & Applied Earth Sciences; Civil Engineering; Environment, general; Geoengineering, Foundations, Hydraulics